Proportion of sewage sludge to soil influences the survival of Salmonella Dublin, and Escherichia coli - Ellis, Stephanie; Tyrrel, Sean; O'Leary, Emma; Richards, Karl; Griffiths, Bryan; Ritz, Karl (Wiley, 2018)
The survival of enteric pathogens in sewage sludge could lead to their transferral into the soil environment and subsequent contamination of crops and water courses. This, in turn, could increase the potential spread of gastrointestinal disease. This work aimed to determine the persistence of several microorganisms, co-introduced with sewage sludge, when exposed to varying proportions of sewage sludge to soil. Three microcosm-based studies were established, inoculated with Salmonella Dublin or an environmentally-persistent strain of Escherichia coli (quantified periodically over a period of 42 days), or indigenous sewage sludge E. coli (quantified over a period of 56 days). Treatments consisted of a mixture containing: 0, 15, 25, 50, 75 and 100% soil or sludge, depending upon the experiment. Each introduced microorganism declined significantly over time, with greater quantities of soil generally instigating greater die-off particularly in the cases of environmentally-persistent E. coli and S. Dublin. However, this relationship was not proportionally related as sludge/soil mixtures showed greater declines than pure soil treatments. In contrast, indigenous sewage sludge E. coli had a more consistent decline across all treatments. This may indicate that indigenous strains are more resilient and may be indicative of natural behaviour. Moreover, the effects of soil-borne factors on pathogen attenuation were context dependent and non-linear, possibly arising from the relative spatial distribution of introduced sludge and attendant microbes in soil.